As tramas cotidianas da acessibilidade no ensino superior: uma etnografia do Programa Agentes de Acessibilidade da Universidade Federal do Ceará (UFC) - Andrade, Abraão Ferreira Monteiro (2024)
This dissertation aims to describe and analyze the practices of the Accessibility Agents from the Accessibility Agents Committee at the Federal University of Ceará (UFC) from an ethnographic perspective. Created in 2019, the committee has been a key ally of the Accessibility Secretariat in the practical implementation of university inclusion for People with Disabilities (PwD). After the expansion of access driven by the inclusion of PwD in the quota policy (2016), the challenge in Higher Education has increased, revealing the gaps between inclusion policy and its practice within the institution. Through Participant Observation conducted by the agent at the Institute of Marine Sciences – Labomar/UFC, it has been possible to trace some of the pathways involved in the inclusion of PwD at UFC and to observe that the meaning of accessibility is not predefined; it must be rearticulated through the agents' practices in challenging contexts marked by uncertainty and instability, where institutional rules do not stand on their own but rely on the agents' engagement with them. Daily dialogues and ethnographic interviews, developed through the researcher's relationship with the field, complement the perceptions of the agent's participant observation.